2020
DOI: 10.3389/fmicb.2020.01366
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Gut Microbiota Across the Life Cycle of Grapholita molesta (Lepidoptera: Tortricidae)

Abstract: Grapholita molesta , the oriental fruit moth, is a serious global pest of many Rosaceae fruit trees. Gut microorganisms play important roles in host nutrition, digestion, detoxification, and resistance to pathogens. However, there are few studies on the microbiota of G. molesta , particularly during metamorphosis. Here, the diversity of gut microbiota across the holometabolous life cycle of G. molesta was investigated comprehensively by Illumina high-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 81 publications
10
63
0
Order By: Relevance
“…At the phylum level, there were no significant differences in the bacterial composition of G. molesta across the five diets of apples, peaches, nectarines, crisp pears, and peach shoots, but the diversity of gut bacteria was significantly lower than that of the artificial feed and plums. In these five treatments, Proteobacteria was the absolute dominant phylum, and its relative abundances were more than 90%, similar to previous researches [20,31,33]. However, in the two treatment groups that fed on an artificial feed and plums, the following four phyla were dominant: Proteobacteria, Firmicutes, Bacteroidota, and Actinobacteriota.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…At the phylum level, there were no significant differences in the bacterial composition of G. molesta across the five diets of apples, peaches, nectarines, crisp pears, and peach shoots, but the diversity of gut bacteria was significantly lower than that of the artificial feed and plums. In these five treatments, Proteobacteria was the absolute dominant phylum, and its relative abundances were more than 90%, similar to previous researches [20,31,33]. However, in the two treatment groups that fed on an artificial feed and plums, the following four phyla were dominant: Proteobacteria, Firmicutes, Bacteroidota, and Actinobacteriota.…”
Section: Discussionsupporting
confidence: 87%
“…Grapholita molesta, known as the oriental fruit moth, is an important fruit tree pest widely distributed in the fruit-growing areas of Asia, Europe, America, Australia, and Africa [17][18][19][20]. It has the characteristic of host shifting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the gut microbial communities were more similar between the female and male adults than that of larvae, indicating that the host developmental stage could influence the microbial community. This result was consistent with studies on Lepidopteran holometabolous insects (Wang et al, 2020). The gut bacterial and fungal community structures and diversity were similar between female and male adults of S. noctilio, which was in agreement with previous findings in Laodelphax striatellus, although Hemiptera is hemimetabolous insect (Bing et al, 2020).…”
Section: Contribution Of Gut Bacteria and Fungi To S Noctilio Larvalsupporting
confidence: 92%
“…However, a crucial consideration for Lepidoptera and other insects that undergo complete metamorphosis is that microbial associations may change between life stages (10). In Lepidoptera, larvae and adults do often differ in the composition and absolute abundance of their microbiomes (6,(11)(12)(13)(14)(15). Beyond this pattern, however, the ecology of adult-stage microbiomes remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%